Reminders of Everyday Misinformation Statements Can Enhance Memory for and Beliefs in Corrections of Those Statements in the Short Term - Wahlheim, Christopher N.; Alexander, Timothy R.; Peske, Carson D. (Psychological science, 2020)
Fake-news exposure can cause misinformation to be mistakenly remembered and believed. In two experiments (Ns = 96), we examined whether reminders of misinformation could improve memory for and beliefs in corrections. Subjects read factual statements and misinformation statements taken from news websites and then read statements that corrected the misinformation. Misinformation reminders appeared before some corrections but not others. Subjects then attempted to recall facts, indicated their belief in those recalls, and indicated whether they remembered corrections and misinformation. In Experiment 1, we did not constrain subjects’ report criteria. But in Experiment 2, we encouraged conservative reporting by instructing subjects to report only information they believed to be true. Reminders increased recall and belief accuracy. These benefits were greater both when misinformation was recollected and when subjects remembered that corrections had occurred. These findings demonstrate one situation in which misinformation reminders can diminish the negative effects of fake-news exposure in the short term.